Drug use and the practice of physical activity in teenagers: a narrative review. - Raúl Polo-Gallardo; Roberto Rebolledo Cobos; Martha Mendinueta-Martinez; Karina Reniz Acosta (Revista de la Facultad de Ciencias de la Salud, 2017)
Drug use in adolescents is a problem that is increasing, negatively affecting the psychophysical health and social development of the adolescent. Health education in adolescents is based on the use of varied teaching-learning strategies that promote behavior change, having a positive impact on drug use in teens. In parallel, regular physical activity has a positive influence on prevention and drug use in this population. This narrative review aims to associate the behavior of adolescents who consume psychoactive substances, health education and practice regular physical activity, based on the most conspicuous international literature. Relevant scientific papers were searched in PubMed, Scopus and Ovid data. Studies published in Spanish, English or Portuguese to provide an objective approach in carrying out the epidemiological, conceptual context and critical-purposing the article were selected. Although the evidence supports the strategies of health education on the behavior of drug use in adolescents, no evidence linking this strategy with the planned physical activity in adolescents are, although there is the conceptual basis that justifies its implementation